Analysis of risk factors and treatment outcome following methotrexate therapy in ectopic pregnancy - Amudha, Paneerselvam; G., Shenbagam; C., Raji (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Ectopic pregnancy is a significant cause of morbidity and mortality in first trimester of pregnancy. Awareness regarding risk factors for ectopic pregnancy aids in early diagnosis and timely medical intervention before tubal rupture occurs. This study was undertaken to analyze the risk factors for ectopic pregnancy and to study the treatment outcome following methotrexate therapy. Methods: In this prospective study, 34 women with unruptured ectopic pregnancy selected for medical therapy were enrolled women with ectopic pregnancy who were hemodynamically stable with initial beta-human chorionic gonadotropin (β hCG) values of <5000 mIU/l, ectopic gestation mass size <5 cm and with no contraindication for methotrexate use were included in the study. Risk factors for ectopic pregnancy were studied and treatment outcome following single dose or 2 dose methotrexate regimen were analyzed. Results: The mean age of the study group was 26.88±4.5 years. Highest incidence of ectopic pregnancy was noted in 26-30 years and in second gravidas. Successful treatment outcome was observed in 61.8% with single dose methotrexate (MTX) and in 23.5% with 2 doses. Overall success rate of MTX therapy was 85.3%. Surgical intervention was instituted in 14.7% when pretreatment β hCG levels were <1500 mIU/ml. Single dose MTX was successful in 91.7% and with 2 doses it was 100%. None developed any major side effects to methotrexate therapy. Conclusions: MTX therapy is safe and effective in carefully selected women with ectopic pregnancy. Success rate of MTX therapy was 85.3%. MTX was most effective when pretreatment β hCG levels were less than 1500 mIU/ml.